Heterogeneous photoredox synthesis of N-hydroxy-oxazolidinones catalysed by metal–organic frameworks. Issue 14 (26th April 2016) - Logan, Matthew W.; Lau, Yuen A.; Zheng, Yongsheng; Hall, Elizabeth A.; Hettinger, Michelle A.; Marks, Randal P.; Hosler, Matthew L.; Rossi, Francis M.; Yuan, Yu; Uribe-Romo, Fernando J.
Abstract : The photocatalytic conversion of N -hydroxy-carbamates to N -hydroxy-oxazolidinones using metal–organic frameworks is reported herein. Abstract : The photoredox conversion of organic functional groups into useful products without the reliance on expensive transition metal-based catalysts has been a major challenge. Here we report the photocatalytic conversion of N -hydroxy-carbamates into N -hydroxy-oxazolidinones using simple metal organic frameworks (MOFs) such asMIL-125-NH2 andUiO-66-NH2 as catalysts in aerobic conditions, with efficiencies and yields comparable to those performed using ground state catalysts. Through sampling increasingly complex structures of carbamates, we found that MOFs induce diasteroselectivities similar to those obtained in solution, which is pivotal in synthesizing natural products and pharmaceuticals, and that the photo-conversion occurred on or near the surface of MOF particles. To provide better mechanistic interpretations on these observations, kinetics studies, quantum yield measurements, and the determination of the photogenerated reactive species were performed. The temperature dependency in the kinetic studies enabled us to identify the photo-redox process as the rate-limiting step of the reaction, a trend that is consistent with using non-porous heterogeneous catalysts like TiO2 . The structural traits of the studied MOFs explain how porosity and light absorption can be tuned for better photocatalysts for achieving high yields and selectivities.